2021
DOI: 10.1029/2020gh000350
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Pathways of Nontuberculous Mycobacteria Through Soil, Streams, and Groundwater, Hawai'i, USA

Abstract: Although uncommon, nontuberculous mycobacterial (NTM) pulmonary infection in the Hawaiian Islands has a relatively high incidence and mortality compared to the mainland U.S. As a result, this study examines the possible geological and hydrological pathways by which NTM patients may become infected, including the environmental conditions that may favor growth and transport. Previously suggested infection routes include the inhalation of NTM attached to micro-droplets from infected home plumbing systems and aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In regions where vanadium concentrations are high, NTM abundance (or more pathogenic species) is likely increased in the water supply, thereby increasing the overall risk of exposure and infection. In a previous study in HI, Nelson et al 43 examined possible routes that NTM may take from the environment into groundwater, subsequently into the public water supplies, and ultimately into homes. The authors demonstrated through aquifer flow models that NTM may survive within the water supply over the course of months via interconnected fractured basalt networks before entering domestic water supplies.…”
Section: Discussionmentioning
confidence: 99%
“…In regions where vanadium concentrations are high, NTM abundance (or more pathogenic species) is likely increased in the water supply, thereby increasing the overall risk of exposure and infection. In a previous study in HI, Nelson et al 43 examined possible routes that NTM may take from the environment into groundwater, subsequently into the public water supplies, and ultimately into homes. The authors demonstrated through aquifer flow models that NTM may survive within the water supply over the course of months via interconnected fractured basalt networks before entering domestic water supplies.…”
Section: Discussionmentioning
confidence: 99%
“…Hawai’i has more NTM lung disease cases per capita than any other US state [ 5 ]. Our prior research of 62 households found that clinically important NTM species are prevalent in the Hawai’i environment [ 6 ] and may be the source of the high rate of NTM infections [ 7 , 8 ]. To more broadly study NTM diversity, a Hawai’i-based community science network involving more than 200 local students and teachers from 11 different schools collected more than 2,800 environmental samples from across O’ahu, Kaua’i, Hawai’i Island, and Maui [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…abscessus , from Hawai'i household water biofilms and garden soil with a predominance of Mycobacterium intracellulare subsp. chimaera (referred to as M. chimaera henceforth), whose common recovery mirrored Hawai'i respiratory specimens (Honda et al., 2016 ; Nelson et al., 2021 ; Virdi et al., 2021 ). We also demonstrated that the indoor environments of Hawai'i are more likely to harbor respiratory relevant NTM compared to outdoor environments, particularly for M. chimaera (Virdi et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wetlands, specific soil components, and geospatial variables have all been correlated with NTM presence in outdoor niches of Hawai'i (Glickman et al., 2020 ; Nelson et al., 2021 ; Virdi et al., 2021 ). However, a unique environmental feature of Hawai'i is active volcanism, including the Kīlauea Volcano on Hawai'i Island.…”
Section: Introductionmentioning
confidence: 99%